2023
DOI: 10.3390/fermentation9030234
|View full text |Cite
|
Sign up to set email alerts
|

Non-Lactic Probiotic Beverage Enriched with Microencapsulated Red Propolis: Microorganism Viability, Physicochemical Characteristics, and Sensory Perception

Abstract: This work aimed to develop a non-dairy functional beverage fermented with probiotic strains and fortified with Brazilian red propolis (microencapsulated and extracted). The non-dairy matrix consisted of oats (75 g), sunflower seeds (175 g), and almonds (75 g). It was fermented by a starter co-culture composed of Lactiplantibacillus plantarum CCMA 0743 and Debaryomyces hansenii CCMA 176. Scanning electron microscopy analysis was initially performed to verify the integrity of the microcapsules. The viability of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 80 publications
1
6
0
Order By: Relevance
“…The average size of the microcapsules was 20 µm, and they exhibited a relatively homogeneous size distribution, except for some agglomerates, which are typical for the spray-drying process. The size and morphology were similar to those of red microcapsules obtained by Ferreira et al [34]. However, the average size and morphology were quite different from what was obtained by Zhang et al [13], using gum arabic and beta-cyclodextrin, but were within the range observed by Ligarda-Samanez et al [14].…”
Section: Discussionsupporting
confidence: 80%
“…The average size of the microcapsules was 20 µm, and they exhibited a relatively homogeneous size distribution, except for some agglomerates, which are typical for the spray-drying process. The size and morphology were similar to those of red microcapsules obtained by Ferreira et al [34]. However, the average size and morphology were quite different from what was obtained by Zhang et al [13], using gum arabic and beta-cyclodextrin, but were within the range observed by Ligarda-Samanez et al [14].…”
Section: Discussionsupporting
confidence: 80%
“…Kefir is a fermented mildly effervescent beverage. The fermentation process for kefir is conducted by a natural microbiota present in the polysaccharide matrix of kefir [ 23 , 24 , 25 , 26 , 27 , 28 , 38 , 39 ]. Kefir grains are a symbiotic association composed mainly of yeasts, lactic acid bacteria and acetic acid bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Kefir grains are a symbiotic association composed mainly of yeasts, lactic acid bacteria and acetic acid bacteria. Kefir grains range in size from 0.5–3.5 cm in diameter, have an irregular shape, and a yellowish or whitish color [ 27 , 28 , 29 , 30 , 31 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations